Вы находитесь на странице: 1из 7

# .

I) .
x 4 4 x 3 19 x 2 + 106 x 120 = 0
x = 2 -
( x 3 2 x 2 23 x + 60)( x 2) = 0

x = 3 -
( x 2 + x 20)( x 3)( x 2) = 0
( x 4)( x + 5)( x 3)( x 2) = 0

: -5;2;3;4

II) .
a0 x n + a1 x n 1 + a 2 x n 2 + ... + a n 1 x + a n = 0

,
, .. a0 = a n , a1 = a n 1 , a 2 = a n 2
1) .
2x 4 + 9x3 x 2 + 9x + 2 = 0
.. x = 0 - , x 2 0 .
9 2
2x 2 + 9x 1 + + 2 = 0
x x
1
1
2( x 2 + 2 ) + 9( x + ) 1 = 0
x
x

.
x +

1
1
= y , x 2 + 2 = y 2 2 ,
x
x
y1 = 5 ; y 2 =

2 y 2 +9 y 5 = 0

1
2

.
1
= 5
x
x 2 + 5 x +1
=0
x

x+

5 21
2
5 21
: x1, 2 =
2
x1, 2 =

1 1
=
x 2
2x 2 x + 2
=0
2x
x+

2) .

, . 1
x 7 + 2 x 6 5 x 5 13 x 4 13 x 3 5 x 2 + 2 x + 1 = 0
x = 1 - .
( x + 1)( x 6 + x 5 6 x 4 7 x 3 6 x 2 + x + 1) = 0

x = 1

x 6 + x5 6x 4 7 x3 6x 2 + x + 1 = 0
. x = 0 - ,
x 3 0
6 1 1
x3 + x 2 6x 7 + + 2 + 3 = 0
x x
x
1
1
1
( x 3 + 3 ) + ( x 2 + 2 ) 6( x + ) 7 = 0
x
x
x

x +

1
1
1
= y , x 2 + 2 = y 2 2 , x 3 + 3 = y 3 3 y ,
x
x
x

y 3 + y 2 9 y 9 = 0

( y +1)( y 3)( y + 3) = 0
y = 1

: x = 1 , x1, 2

III)

y =3

1
x + = 1
x
2
x + x +1
=0
x

y = 3

1
x + =3
x
2
x 3 x +1
=0
x

1
x + = 3
x
2
x + 3x +1
=0
x

3 5
2
3 5
3 5
=
, x 3, 4 =
2
2
x1, 2 =

ax + bx + cx + dx + l = 0 ,
4

x 3, 4 =

3 5
2

a b2
=
l d2

.
IV) .
V) .
1
2

x 4
x 2
x +2
5
=0
44
+12 2
x 1
x +1
x 1
2

x 2
x +2
=U ,
= V ,
x +1
x 1
5U 2 44V 2 + 12UV = 0
1) V = 0 , U = 0 ,

x 2
x + 1 = 0

x+ 2 = 0
x 1

x= 2

x= 2

2) V 2 0 ,
2

U
U
5 +12 44 = 0
V
V

U
,
V

U
U
22
=2;
=
V
V
5
U = 2V ; 5U = 22V

.
x 2 2( x + 2)
=
x +1
x 1
x 2 + 9x + 2 = 0

5( x 2)
22( x + 2)
=
x +1
x 1
9 x 2 + 17 x + 18 = 0

9 73
2
9 73
: x1, 2 =
2
x1, 2 =

2.
5x
5 x
x
x +
=6
x 1
x +1
x + 1
5x
5x
=U , x +
= V , UV = 6
x
x +1
x +1
5x
5x
+x+
=5
U + V = x
x +1
x +1

UV = 6

U + V = 5

U1 = 3

V1 = 2

U2 = 2

V2 = 3

5 x
x x + 1 = 3

x + 5 x = 2
x + 1

5 x
x x + 1 = 2

x+ 5 x = 3
x + 1

x 2 2 x + 3 = 0
2
x 2 x + 3 = 0

x 2 3x + 2 = 0
2
x 3x + 2 = 0

x1 = 2 ; x 2 = 1

: x1 = 2 ; x2 = 1
3.
2( x 2 + x +1) 2 7( x 1) 2 = 13( x 3 1)

x =1 -

( x 1) 2 0 ,
x 2 + x +1
x 2 + x +1
7 13
2
=0
x 1
x 1

x 2 + x +1
= y ,
x 1

2 y 2 13 y 7 = 0

y1 = 7 ; y 2 =
x 2 + x +1
=7
x 1
x 2 6x + 8 = 0

1
2

x 2 + x +1
1
=
x 1
2
2
2 x + 3x + 1 = 0

x1 = 4 ; x 2 = 2

x3 = 1 ; x 4 =

: x1 = 4 ; x 2 = 2 ; x3 = 1 ; x4 = 1 / 2

1
2

## VI) ( x a)( x b)( x c)( x d ) = k , a + b = c + d

( x a )( x b) ( x c)( x d ) , .
Ax

Bx

VII) ax 2 + b x + c + ax 2 + b x + c = k
1
2
,
.
3x
5x
2
+ 2
=
2 x + 5 x + 2 2 x + 11x + 2 3
3x

x 2 x + 5 +
x

5x

1 11 105
x 2; ;
2
2

(1)

2
3

(2)
x 2 x + 11 +
x

(1) ( 2) x 0 . ,
x = 0 . .
3
5
2
+
=
2
2 3
2x + 5 +
2 x + 11 +
x
x

.
2 x + 5 +

2
2
= y , 2 x + 11 + = y + 6 ,
x
x

3
5
2
+
=
y y +6 3

y1 = 9 ; y 2 = 3
2
2x + 5 + = 9
x
2
2x 4x + 2 = 0
x1 =1

2
= 3
x
2 x 2 + 8x + 2 = 0
2 x +11 +

x 2 , 3 = 2 3

: x1 =1 ; x2,3 = 2 3

## VIII) (ax 2 + b1 x + c)(ax 2 + b2 x + c) = kx 2

x 2 0
( 2 x 2 3 x +1)(2 x 2 + 5 x +1) = 9 x 2

x = 0 - . x 2 0 ,
1
1

2 x 3 + 2 2 x + 5 + 2 = 9
x
x

.
1
1
2 x 3 + 2 = y ; 2 x + 5 + 2 = y + 8 ,
x
x
y 2 +8 y 9 = 0

y1 = 9 ; y 2 = 1
1
2 x 3 + 2 = 9
x

3 7
2
3 7
2 2
: x1, 2 =
; x3, 4 =
2
2
x1, 2 =

IX) .

2x 3 +
x3, 4 =

1
=1
x2

2 2
2

x2 +

81x 2
= 40
(9 + x) 2

x 9

9x
2 9x 2

= 40
x
+
9+x
9+x

9x
x2

= 40
x
+18
9+x
9+x

x2
= y ,
9+x

y 2 +18 y 40 = 0

y1 = 2 ; y 2 = 20

.
x2
=2
9+x
x 2 2 x 18 = 0

x2
= 20
9+x
x 2 + 2 x + 180 = 0

x1, 2 = 1 19

: x1, 2 = 1 19

X)

( a 2 b 2 ) = ( a b)(a + b)

x 4 + 4 x 3 + 3x 2 + 2 x 1 = 0
x 4 + 4x3 + 4x 2 x 2 + 2x 1 = 0
( x 2 + 2 x ) 2 ( x 1) 2 = 0

( x 2 + 2 x + x 1)( x 2 + 2 x x +1) = 0

x 2 + 3x 1 = 0
x1, 2 =

3 13
2

XI)

x 2 + x +1 = 0

( x a ) n + ( x b) n = k
a +b
y =x
2

( x + 3) 4 + ( x + 5) 4 = 16

.
y = x + 4 ,
( y 1) 4 + ( y +1) 4 = 16
( y 2 2 y + 1) 2 + ( y 2 + 2 y + 1) 2 = 16
y 4 + 4 y 2 + 1 4 y 3 + 2 y 2 4 y + y 4 + 4 y 2 + 1 + 4 y 3 + 4 y + 2 y 2 = 16
y4 +6y2 7 = 0
y 2 =1
y 2 = 7 < 0

y1 = 1 ; y 2 = 1
.

x + 4 =1

x1 = 3
: x1 = 3 ; x 2 = 5

x + 4 = 1
x 2 = 5

XII) .
x6 7x2 + 6 = 0
x 6 (( 6 ) 2 +1) x 2 + 6 = 0
x6 x2 ( 6)2 x2 + 6 = 0
x 2 ( 6)2 6 x 2 x6 = 0

b = 1

a = x2

c = x2 x6

D = 1 4 x 2 ( x 2 x 6 ) = 1 4 x 4 + 4 x 8 = ( 2 x 4 1) 2
6=
2

1 2 x 4 1

6x

2x 2
2

=1 2 x

2 6x

2 6 x 2 =1 2 x 4 +1
x 4 + 6 x 2 1 = 0

x2 =

2x 2
2

=1 + 2 x 4 1

2 6 x 2 =1 + 2 x 4 1
x4 6x2 = 0

6 10
6 + 10
< 0 ; x2 =
2
2

6=

1 + 2 x 4 1

x1, 2 =

6 + 10
2

x = 0 -
x2 = 6

x3, 4 = 4 6

: x1, 2 = 6 + 10 ; x3, 4 = 4 6
2

XIII) .
x +1 x 2 x 3 x + 4
+
+
+
=4
x 1 x + 2 x + 3 x 4
x 1 + 2 x + 2 4 x + 3 6 x 4 + 8
+
+
+
=4
x 1
x+2
x +3
x4
2
4
6
8
1+
+1
+1
+1 +
=4
x 1
x+2
x +3
x 4
1
2
3
4

+
=0
x 1 x + 2 x + 3 x 4
x 4 + 4 x 1 2 x + 6 + 3 x + 6

=0
( x 1)( x 4)
( x + 2)( x + 3)
5 x 8
5 x +12

=0
( x 1)( x 4) ( x + 2)( x + 3)
5 x 2 + 5 x 16 = 0

5 345
10
5 345
: x1, 2 =
10
x1, 2 =

x 1;
2;
3;4